Pengaruh Model Pembelajaran Conceptual Understanding Procedures (CUPs) Berbantuan LKPD Terhadap Penguasaan Konsep Fisika Peserta Didik - Ibrahim Ibrahim; Kosim Kosim; Gunawan Gunawan; Rahmatullah Rahmatullah (Indonesian, 2021)
A common problem that occurs in students is the lack of ability to understand concepts. This is because the physics learning process does not vary. So that innovative learning design efforts are needed. One of the efforts that can be done is by using the CUPs learning model assisted by LKPD. This study aims to determine the effect of learning model Conceptual Understanding Procedures LKPD assisted towards the student’s concept mastery in physics of high school. This research is a quasi experimental research using untreated control group design with pretest and posttest. The population is all students of class XI IPA SMAN 4 Mataram. While the sampling using purposive sampling technique consisting of students’ class XI IPA 4 as experimental class and students of class XI IPA 1 as a control class. The concept mastery data is obtained through a written test in the form of a description item. The result of hypothesis test analysis shows that there is influence of learning model of LKPD-assisted Conceptual Understanding Procedures toward the student’s concept mastery in physics of high school.